Early Signs of Autism - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
A blinded comparison of parental and clinical observations of the behavior of 26 autistic children (23 boys and 3 girls) younger than age 48 months is reported from the Vanderbilt University School of Medicine, Nashville, TN, and The Children's Mercy Hospital, Kansas City.